2002
DOI: 10.1101/gad.969202
|View full text |Cite
|
Sign up to set email alerts
|

E2F mediates cell cycle-dependent transcriptional repression in vivo by recruitment of an HDAC1/mSin3B corepressor complex

Abstract: Despite biochemical and genetic data suggesting that E2F and pRB (pocket protein) families regulate transcription via chromatin-modifying factors, the precise mechanisms underlying gene regulation by these protein families have not yet been defined in a physiological setting. In this study, we have investigated promoter occupancy in wild-type and pocket protein-deficient primary cells. We show that corepressor complexes consisting of histone deacetylase (HDAC1) and mSin3B were specifically recruited to endogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
277
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(296 citation statements)
references
References 49 publications
18
277
1
Order By: Relevance
“…Previous ChIP studies indicated that E2F members occupied gene promoters in a cell cycle-specific manner, suggesting their specific roles during the cell cycle through coordinated targeting and regulation of specific genes (Takahashi et al, 2000;Wells et al, 2000;Rayman et al, 2002). Together with other reports indicating multiple promoter occupancies that lead to both positive and negative transcriptional activation thresholds , we suggest a physiological role for E2F4 in the radiation-dependent stable G 2 arrest, just as exogenous E2F 1-3a can promote cell cycle progression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous ChIP studies indicated that E2F members occupied gene promoters in a cell cycle-specific manner, suggesting their specific roles during the cell cycle through coordinated targeting and regulation of specific genes (Takahashi et al, 2000;Wells et al, 2000;Rayman et al, 2002). Together with other reports indicating multiple promoter occupancies that lead to both positive and negative transcriptional activation thresholds , we suggest a physiological role for E2F4 in the radiation-dependent stable G 2 arrest, just as exogenous E2F 1-3a can promote cell cycle progression.…”
Section: Discussionmentioning
confidence: 99%
“…They are believed to accomplish this by recruiting a variety of chromatin-modifying activities to E2F-responsive promoters (Frolov and Dyson, 2004). Pocket proteins recruit type I histone deacetylases (HDACs), resulting in removal of acetyl groups from histones H3 and H4, and in a compacted chromatin structure that is refractory to transcription initiation (Takahashi et al, 2000;Rayman et al, 2002). The recruitment of HDACs is indirect (Lai et al, 2001) and accompanied by recruitment of other co-repressors, chromatin remodelling factors and histone methyltransferases (Frolov and Dyson, 2004).…”
Section: Retinoblastoma Gene Familymentioning
confidence: 99%
“…E2F4 and E2F5 then relocate to the cytoplasm, and the promoters generally bind to E2F1-3. For many promoters, the binding of E2F1-3 correlates with recruitment of histone acetyltransferases, increased histone acetylation and transcriptional activation (Takahashi et al, 2000;Rayman et al, 2002;Taubert et al, 2004). A model for pRb2/p130 and p107 control during cell proliferation has been proposed based on experimental data.…”
Section: Retinoblastoma Gene Familymentioning
confidence: 99%
“…The pocket proteins bind a number of chromatin modifying factors that may account for transcriptional repression by E2F complexes (reviewed by Cobrinik (2005)). For example, pocket protein/E2F complexes recruit histone deacetylases (HDACs) to remove acetyl groups from histones H3 and H4 (Rayman et al, 2002), resulting in a more compact chromatin structure that inhibits transcription initiation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies of endogenous promoters in mouse cells lacking E2F and/or pocket proteins, and in human cells expressing viral oncoproteins such as E1A, are complicated by the fact that these cells suffer profound phenotypic changes affecting cell cycle regulatory processes. Previously, we generated stable NIH 3T3 cell lines carrying low copy numbers of an integrated B-myb promoter-regulated reporter and showed that the E2F site is required for recruitment of p130 and HDAC-1 to repress this gene following serum starvation (Rayman et al, 2002). To allow investigation of promoter regulation in its natural chromatin context, we have now introduced an E2F site mutation into the endogenous B-myb promoter in mouse embryonal stem (ES) cells and have generated mice carrying this mutant allele.…”
Section: Introductionmentioning
confidence: 99%